Sri Lanka : Request for Extension of Repurchase Expectations. (IMF Staff Country Reports; Country Report ;, 2005)
This paper examines Sri Lanka's Request for Extension of Repurchase Expectations. The Sri Lankan authorities request an extension of repurchase expectations arising in the remainder of 2005, in the amount of SDR 74,162,500. The extension would have the effect of moving the repurchase expectations to an obligations basis, with each amount falling due exactly one year after the expectation date. The authorities have also expressed their desire to resume discussions on the Poverty Reduction and Growth Facility (PRGF)/EFF-supported program.